2001
DOI: 10.1161/01.cir.104.3.292
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dofetilide in the Treatment of Atrial Fibrillation-Flutter in Patients With Reduced Left Ventricular Function

Abstract: Dofetilide is safe and increases the probability of obtaining and maintaining sinus rhythm in patients with structural heart disease. The present study suggests that restoration of sinus rhythm is associated with improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(75 citation statements)
references
References 21 publications
3
70
0
2
Order By: Relevance
“…These findings are consistent with those of the DIAMOND Study, in which the presence of SR throughout that trial was associated with improved survival. 4 Because of the retrospective, nonrandomized nature of the analyses, however, neither the DIA-MOND Study nor ours can distinguish whether SR is an important determinant of survival or a marker for other factors associated with survival that were not recorded, determined, or included in the survival model.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These findings are consistent with those of the DIAMOND Study, in which the presence of SR throughout that trial was associated with improved survival. 4 Because of the retrospective, nonrandomized nature of the analyses, however, neither the DIA-MOND Study nor ours can distinguish whether SR is an important determinant of survival or a marker for other factors associated with survival that were not recorded, determined, or included in the survival model.…”
Section: Discussionmentioning
confidence: 87%
“…3 In a series of trials assessing the efficacy and safety of dofetilide to treat AF, the Danish Investigations of Arrhythmia and Mortality on Dofetilide (DIAMOND) studies showed that patients who had SR either with or without AAD therapy had a superior prognosis compared with patients with continued AF. 4 Thus, the possibility arose that the presence or absence of SR itself, rather than treatment strategy, is responsible for outcome.…”
mentioning
confidence: 99%
“…33,34 Because of the risk of torsade de points within first three days, therapy with dofetilide requires in-hospital initiation with close monitoring of the QT interval and dosage adjustments in patients with impaired renal function.…”
Section: 12mentioning
confidence: 99%
“…33, 34 Zbog rizika od razvoja torsades de pointes unutar prva tri dana, liječenje dofetilidom mora se započeti u bolnici uz pažljivo praćenje QT intervala i prilagođenja doze u bolesnika s oštećenom bubrežnom funkcijom .…”
Section: 30unclassified
“…Although rate control was found to be superior to rhythm control in AFFIRM and RACE, subsequent analyses suggested a benefit of maintaining sinus rhythm, which was completely offset by the toxicity of anti-arrhythmic drugs (57,58). One technique of achieving sinus rhythm without anti-arrhythmic drugs would be curative catheter ablation.…”
Section: Diagnosis and Managementmentioning
confidence: 99%